The Magnitude and “Peanuts” Effects: Searching Implications - Cruz Rambaud, Salvador; Sánchez Pérez, Ana M. (Frontiers in Applied Mathematics and Statistics, 2018)
The framework of this paper is the field of decision-making processes in which people face the choice of probabilistic or dated rewards. Traditionally, the preferences for probabilistic outcomes have been analyzed by the Expected Utility (EU) model whilst the preferences for dated rewards have been studied by the Discounted Utility (DU) model. Nevertheless, recent empirical findings have revealed the existence of several anomalies or paradoxes in both contexts. Specifically, EU and DU models exhibit an anomaly affecting the amount of the reward, viz the peanuts and the magnitude effects, respectively, which seem go in opposite directions. The aim of this paper is to jointly analyze both effects in a wide setting involving choices under risk and over time, searching implications between both anomalies